2008
DOI: 10.1111/j.1365-2478.2007.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐correlation of random fields: mathematical approach and applications

Abstract: International audienceRandom field cross-correlation is a new promising technique for seismic exploration, as it bypasses shortcomings of usual active methods. Seismic noise can be considered as a reproducible, stationary in time, natural source. In the present paper we show why and how cross-correlation of noise records can be used for geophysical imaging. We discuss the theoretical conditions required to observe the emergence of the Green's functions between two receivers from the cross-correlation of noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
139
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 68 publications
0
139
1
6
Order By: Relevance
“…The averaging time needed for a reliable retrieval of a deterministic timefront from the NCCF was found to range from several hours at horizontal separations of ∼0.5 km to ∼40 hours at the largest horizontal separation of 3.5 km. These values are larger than theoretical estimates [Gouédard et al, 2008;Zabotin and Godin, submitted manuscript, 2009] of ∼10 min and ∼8 hours, respectively, obtained assuming diffuse, isotropic noise. The difference is the result of a preponderance of localized noise sources at the experimental site.…”
Section: Noise Cross-correlation Functioncontrasting
confidence: 39%
“…The averaging time needed for a reliable retrieval of a deterministic timefront from the NCCF was found to range from several hours at horizontal separations of ∼0.5 km to ∼40 hours at the largest horizontal separation of 3.5 km. These values are larger than theoretical estimates [Gouédard et al, 2008;Zabotin and Godin, submitted manuscript, 2009] of ∼10 min and ∼8 hours, respectively, obtained assuming diffuse, isotropic noise. The difference is the result of a preponderance of localized noise sources at the experimental site.…”
Section: Noise Cross-correlation Functioncontrasting
confidence: 39%
“…Even in case of partial equipartition it might be possible to extract exact Green's function information (Tsai 2010). In other words, inferring the Green's function is effective after the sufficiently selfaveraging process that is provided by the scattering and random spatial-temporal noise source distribution when sufficiently long time-series are considered (Campillo 2006;Gouédard et al 2008). This means that the required source density for reconstructing the full Green's function is determined by the position and size of the heterogeneous area and heterogeneities with respect to the sources (Derode et al 2003;Fan & Snieder 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using correlational forms of the reciprocity theorems, Wapenaar & Fokemma (2006) showed how inter-receiver Green's functions could be constructed by crosscorrelating recorded fields whereas other studies have also revealed the limitations of that method (Snieder 2004;Roux et al 2005;Gouédard et al 2008). For obtaining a diffuse field Halliday & Curtis (2008) analyse the requirements in terms of source distribution for the retrieval of scattered surface waves.…”
Section: Introductionmentioning
confidence: 99%
“…Wavefields generated by spatially distributed random sources are known to remain partially coherent at points separated by distances that are large compared to the wavelength, with the twopoint cross-correlation function of the random wavefields approximating the Green's function, which describes deterministic wave propagation between the two observation points (Lobkis & Weaver 2001;Snieder 2004;Roux et al 2004;Wapenaar 2004;Godin 2006;Gouédard et al 2008). Cross-correlation functions of pressure fluctuations in the ocean have been investigated in the 0.5-30 mHz band, where the correlations characterize deep-water infragravity waves and their sources (Webb 1986;Godin et al 2014b), and at acoustic frequencies above 1 Hz, where geoacoustic parameters of the seafloor (Brown et al 2014), spatial (Godin et al 2010) and temporal (Woolfe et al 2015) variations of the sound speed in water and ocean current velocity (Godin et al 2014a) have been retrieved from noise cross-correlations.…”
Section: Introductionmentioning
confidence: 99%